A Companion to comparative literature - Behdad, Ali 1961-; Thomas, Dominic Richard David (Chichester, West Sussex Wiley-Blackwell, 2011)
"A Companion to Comparative Literature presents a collection of more than thirty original essays from established and emerging scholars, which explore the history, current state, and future of comparative literature. Features over thirty original essays from leading international contributors Provides a critical assessment of the status of literary and cross-cultural inquiry Addresses the history, current state, and future of comparative literature Chapters address such topics as the relationship between translation and transnationalism, literary theory and emerging media, the future of national literatures in an era of globalization, gender and cultural formation across time, East-West cultural encounters, postcolonial and diaspora studies, and other experimental approaches to literature and culture."--Provided by publisher.
Introduction / Ali Behdad and Dominic Thomas -- Part I. Roadmaps. A discipline of tolerance / Rey Chow -- Why compare? / David Ferris -- Method and congruity : the odious business of comparative literature / David Palumbo-Liu -- Comparisons, world literature, and the common denominator / Haun Saussy -- Comparative literature in America : attempt at a genealogy / Kenneth Surin -- Part II. Theoretical directions. The poiein of secular criticism / Stathis Gourgouris -- VAnishing horizons : problems in the comparison of China and the West / Eric Hayot -- Art and literature in the liquid modern age : on Richard Wollheim, Zygmunt Bauman and Yves Michaud / Efraâin Kristal -- A literary object's contextual life / Michael Lucey -- The theater of comparative literature / Sharon Marcus -- Part III. Disciplinary intersections. What pictures tell us about the letter : visual and literary practices in Latin America / Jorge Coronado -- If there's a text in this class, where did it come from? Or, What does Marilyn Monroe have to do with The sorrows of young man Werther? / Richard Maxwell and Toby Miller -- Comparative literature in the age of digital humanities : on possible futures for a discipline / Todd Presner -- Comparing pain : theoretical explorations of suffering and working towards the particular / Zoèe Norridge -- Comparativism, transfers, entangled history : sociological perspectives on literature / Gisáele Sapiro -- Part IV. Linguistic trajectories. Orphaned language : traumatic crossings in literature and history / Cathy Caruth -- Contested grammars : comparative literature, translation, and the challenge of locality / Simon Gikandi -- Comparative literature and the global languagescape / Mary Louise Pratt -- Persian incursions : the transnational dynamics of Persian literature / Nasrin Rahimieh -- Rudimentariness as home / Mireille Rosello -- Part V. Postcolonial mobilities. Afro-European studies : emerging fields and new directions / Allison Crumly Deventer and Dominic Thomas -- The comparative and the relational : meditations on racial method / David Theo Goldberg -- Kidnapped narratives : mobility without autonomy and the nation/novel analogy / Deborah Jenson -- Counterpoint and double critique in Deward Said and Abdelkebir Khatibi : a transcolonial comparison / Franðcoise Lionnet -- How French studies became transnational; or postcolonialism as comparatism / David Murphy -- Towards a planetary reading of postcolonial and American imaginative eco-graphies / Sangeeta Ray -- Part VI. Global connection. Terrestrial humanism : Edward W. Said and the politics of world literature / Emily Apter -- Logics and contexts of circulation / Brian T. Edwards -- "Worlds in collision" : the languages and locations of world literature / Charles Forsdick -- The trouble with world literature / Graham Huggan.
Includes bibliographical references and index.
Keywords: Comparative literature